Empowering functional skills through digital literacy and ICT self-efficacy: Evidence from rural Islamic secondary schools in Pakistan - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah Binti Tunku; Khan, Ammar Saleem (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
In response to the evolving demands of 21st-century education, the cultivation of digital competencies among teachers is critical to enhancing instructional quality and student learning outcomes. Despite growing recognition of the importance of digital literacy and ICT self-efficacy, empirical investigations into their impact on functional skills, such as communication, critical thinking, and problem-solving, remain limited, particularly within rural Islamic secondary schools in Pakistan. This study explores the extent to which digital literacy and ICT self-efficacy predict the development of functional skills among teachers in Kot Addu South, Pakistan. Employing a quantitative survey design, data were collected from 440 Islamic secondary school teachers using a structured questionnaire. Reliability and validity were ensured through expert review and pilot testing, and data analysis was conducted using descriptive statistics, correlation analysis, and t-test regression via SPSS. Findings reveal moderate digital tool utilization among participants, yet those with higher levels of digital literacy and ICT self-efficacy demonstrated significantly greater proficiency in functional skills. Positive and statistically significant correlations were observed between digital literacy and all three domains of functional skills. Although gender-based variations were minimal, both male and female teachers benefitted from enhanced digital capabilities. These results emphasize the strategic importance of fostering digital literacy and ICT self-efficacy through targeted training programs. The study provides valuable insights for educational policymakers, school leaders, and professional development designers to elevate teacher effectiveness and bridge digital inequities in under-resourced educational environments.